Dope Dyed Viscose Fibers from Black Liquor Treated Carbon Black. Issue 1 (January 2020) - Shukla, Neelesh Bharti; Varma, Arati; Sharma, Esha; Sharma, Preetika; Ralebhat, Shrikant; Magare, Bhupendra
Black liquor (BL), a byproduct generated during the kraft pulping process, was used as a source of alkaline lignin (AL) to stabilize aqueous dispersions of carbon black (CB). Black liquor-treated carbon black (BL-CB) samples were prepared by varying the BL/CB/water ratio and characterized by scanning electron microscopy (SEM), thermogravimetric analysis (TGA), and Brunauer-Emmett-Teller (BET) surface area. Improvement in dispersion of BL-CB with increased BL content was observed. The dope dyed viscose fibers were spun by addition of BL-CB to the viscose solution. These fibers exhibited deeper color strength than those obtained from conventional CB formulations at a comparable CB loading on the fiber.